Use of traditional medicine : are we on the right way? - Helal Uddin, A.B.M.; Khalid, Reem S.; Abbas, Syed Atif; Khan, Umeed Ali (2010)
Herbal or traditional remedies have been used to cure different ailments since pre- historic times. The use of recorded herbal medicines can be traced back to about 5000 years ago when the Sumerian's used plants such as thyme and laurel as a remedy for ailments. According to the WHO report at present about 70 to 80 percent of world population is largely depending on traditional medicine (TM). In recent years surprisingly the usage of TM has become popular in developed countries like USA and Europe. In fact mistakenly a large number of the users of traditional medicine think that anything that is prepared from natural sources or elements is safe for consumption and does not have any undesirable side effects. This fallacy is present not only among the users of the poor/developing nations but also the users of developed countries. Toxicity arising from the use of traditional medicine is often reported. It may arise from the ingredients itself or from the process of formulation of the traditional medicine. Lack of supervision and strict control over the formulation procedure is major factor that causes such complication. WHO has expressed its concern about the lack of research on the area for the standardization and quality control issues for the manufacturing of the TM. To ensure the safety and efficacy issues related to the consumption of TM is getting prime attention from the relevant authorities around the world. In our study we are emphasizing on the quality control issues for the manufacturing of TM. It will also highlight some of our study results reported earlier regarding the presence of toxic heavy metals in different traditional medicine preparations collected locally. Our aim is not to put obstacles for the uses of TM rather make people aware to become careful about the use of traditional medicine. Our study is in line with the government’s plan of ensuring GMP in the manufacturing of all forms of medicinal product either conventional or traditional.